2002
DOI: 10.1152/ajpheart.00299.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of ANG II in coronary capillary angiogenesis at the insulin-resistant stage of a NIDDM rat model

Abstract: Jesmin, Subrina, Yuichi Hattori, Ichiro Sakuma, Chishimba N. Mowa, and Akira Kitabatake. Role of ANG II in coronary capillary angiogenesis at the insulin-resistant stage of a NIDDM rat model. Am J Physiol Heart Circ Physiol 283: H1387-H1397, 2002; 10.1152/ajpheart.00299.2002.-With the use of Otsuka Long-Evans Tokushima Fatty (OLETF) rats, a model of human non-insulin-dependent diabetes mellitus (NIDDM), we assessed whether ANG II is involved in coronary capillary angiogenesis at the insulinresistant stage of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 43 publications
(49 reference statements)
4
30
1
Order By: Relevance
“…We also showed a significant increase in cardiac collagen deposition in these diabetic rats, as reported in previous studies from this laboratory. 18,19 Support for our findings is also provided by the results of other investigators who demonstrated that cardiac fibrosis could be promoted from the prediabetic state in OLETF rats. 4 We found that TGF-␤ 1 was highly expressed in coronary vessels and the perivascular area, as well as in cardiomyocytes in the OLETF rat heart.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also showed a significant increase in cardiac collagen deposition in these diabetic rats, as reported in previous studies from this laboratory. 18,19 Support for our findings is also provided by the results of other investigators who demonstrated that cardiac fibrosis could be promoted from the prediabetic state in OLETF rats. 4 We found that TGF-␤ 1 was highly expressed in coronary vessels and the perivascular area, as well as in cardiomyocytes in the OLETF rat heart.…”
Section: Discussionsupporting
confidence: 88%
“…16 Our recent work found that angiotensin II labeling and AT 1 receptor expression in coronary vessels were profoundly increased in Otsuka LongEvans Tokushima Fatty (OLETF) rats, a model of human non-insulin-dependent diabetes mellitus (NIDDM), 17 compared with nondiabetic Long-Evans Tokushima Otsuka (LETO) rats. 18 However, it is not known whether AT 1 receptor blockade can produce a favorable effect on altered expression of molecules associated with ECM turnover and regulation that might contribute to the development of coronary remodeling seen in diabetes. This study aimed to gain insight into the molecular mechanisms underlying coronary remodeling of ECM in the heart observed at the insulin-resistant stage of NIDDM in OLETF rats, and we sought to evaluate the therapeutic effect of candesartan, an AT 1 receptor blocker, on the altered expression of molecules involved in coronary matrix remodeling in diabetic animals.…”
mentioning
confidence: 99%
“…Systemic ACE and AngII levels in diabetic patients are not elevated, although subsets of patients may have elevated ACE activity if they carry the ACE DD polymorphism (45,46). Another possibility is that diabetes stimulates local increases of AngII or AngII receptors within specific tissues or compartments (47). It is now accepted that most tissues contain all of the components of the renin-angiotensin system and are able to generate tissue AngII independent of the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the effect of benidipine therapy to normalize the upregulated ET-1 system in OLETF rat hearts may be partly due to the modestly lowering action on blood pressure. Furthermore, we have previously found that angiotensin II is upregulated in coronary vessels of the OLETF rat heart, and the blockade of angiotensin II type 1 receptors with candesartan can greatly reverse diabetes-induced cardiac remodeling (24). In this regard, angiotensin II can induce ET-1 gene expression in rat aortic smooth muscle cells (21), and angiotensin-converting enzyme inhibition can decrease circulatory ET-1 levels in lean noninsulin-dependent diabetic patients (16).…”
Section: Discussionmentioning
confidence: 98%